Improving pallet control in mass consumption companies: a proposal for layout optimization - Chirinos Ayala, Silvana Paola (2024)
The experimental research will be carried out in a consumption company in Perú. The main problem is the lack of traceability and pallet management in their distribution centers, which leads to an annual loss of 175 thousand dollars. The methodology used was the SLP, particularly the matrix of quantity, distance and effort with the objective of carrying out an adequate layout design and the implementation of a barcode for a correct management and tracking of the pallets. The research will be carried out in distribution center D, reducing the percentage of lost pallets by 18% and showing a savings of 32% in the supply of indirect materials at least annually.